Preventing Internalizing Problems in Young Children: A Randomized Controlled Trial of the Feelings and Friends (Year 3) Program with a Motor Skills Component - Tennant, Ruhamah G.; Martin, Katie K.; Rooney, Rosanna; Hassan, Sharinaz; Kane, Robert T. (Frontiers in Psychology, 2017)
Anxiety and depression are common mental health problems experienced by children in Australia. The impact of these internalising disorders is pervasive, affecting many areas of life. By the time problems have been detected in children they can be severe in nature and harder to treat. Hence, early intervention is of utmost importance. Despite the existence of numerous prevention programs for children, there is limited empirical evidence for a program that has an impact on symptoms of both anxiety and depression. Physical activity and improved motor coordination have been indicated as having positive effects on children’s mental health, although the impact of including these in a program targeting internalising disorders has not been established. This study aimed to evaluate the efficacy of the Feelings and Friends (Year 3) program (FFY3), revised to include activities to build motor-coordination and encourage physical activity. Participants were twenty-four children from the Perth metropolitan area alongside one of each of their parents. Results indicated significant short-term intervention effects on one of the primary outcome variables; intervention group parents reported significant pre-post improvement in child depressive symptoms, which were maintained at three-month follow-up (ηp2 = .10). There were also intervention effects observed for parent-reported separation anxiety (ηp2 = .10), externalising symptoms (ηp2 = .19), and conduct problems (ηp2 = .16). An additional finding indicated the intervention students reported significant improvement from session one to session two in global distress (ηp2 = .22). No other significant intervention effects were evident. Findings from this study indicate that FFY3 is a promising intervention to address internalising and externalising symptoms in 8-9 year-old children.